1987
DOI: 10.1073/pnas.84.6.1487
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of recombinant interleukin 2 by polyethylene glycol increases its potency in the murine Meth A sarcoma model.

Abstract: Recombinant human interleukin 2 purified from Escherichia coli has limited solubility at neutral pH and a short circulatory half-life. This recombinant interleukin 2 was chemically modified by an active ester of polyethylene glycol. The modified interleukin 2 was purified by hydrophobic interaction chromatography and characterized by sodium dodecyl sulfate/polyacrylamide gel electrophoresis and isoelectric focusing. This conjugate was compared to unmodified recombinant interleukin 2 in vitro and in vivo. Coval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
79
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(80 citation statements)
references
References 26 publications
0
79
1
Order By: Relevance
“…23,24 Modifications of peptides or proteins with PEG increase their stability and solubility in the blood and can increase their potency. 25,26 It has already been reported that PIC micelles of DNA with PEG-PLL are highly water soluble, and form nuclease resistant nanoparticles. 18 Moreover, addition of PEG was reported to have reduced cytotoxicity compared with polycation homopolymer.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Modifications of peptides or proteins with PEG increase their stability and solubility in the blood and can increase their potency. 25,26 It has already been reported that PIC micelles of DNA with PEG-PLL are highly water soluble, and form nuclease resistant nanoparticles. 18 Moreover, addition of PEG was reported to have reduced cytotoxicity compared with polycation homopolymer.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical modification of bioactive proteins with polyethylene glycol (PEG) increases their molecular size and steric hindrance, both of which are derived from PEG attached to bioactive proteins, resulting in augmented plasma half-lives and stability (Katre et al, 1987;Hershfield et al, 1991). These PEG-modified bioactive proteins have increased therapeutic potency, so PEGylation enables the therapeutic dose and frequency to be decreased.…”
mentioning
confidence: 99%
“…PEGylation of proteins increases their plasma half-lives by reducing proteolysis and restricting tissue-distribution such as glomerular filtration by the kidney and hepatic uptake (12)(13)(14)(15)(16)(17)(18)(19)(20). This effect is attributed to the increased molecular size and steric hindrance that result from attaching PEG to proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This results in an improvement of plasma half-lives and in proteolytic-stability, and a decrease in immunogenicity and hepatic uptake (13,15). PEGylation of interleukin-2 has been reported to increase its antitumor potency in vivo (16), and PEGylation of an F(abЈ)2 derived from the monoclonal antibody A7 has improved its tumor localization (17). We previously reported that a PEGylated chimeric toxin composed of transforming growth factor-␣ and PE showed an improvement in its blood-residency time and Abbreviation: PE, Pseudomonas exotoxin; PEG, polyethylene glycol.…”
mentioning
confidence: 99%